PENGARUH LAYOUT TEMPAT DUDUK LINEAR DALAM RUANG KULIAH TERHADAP PENYEBARAN KEPADATAN POSISI DUDUK MAHASISWA (Studi Kasus: Ruang Kuliah Jurusan Desain Interior - ITB) - Larasati, Mutiara Ayu (ARTEKS Jurnal Teknik Arsitektur, 2017)
Title: Effect Of Linear Seating Arrangements on Students Seating Preferences Density In The Classroom Seating arrangement in a classroom is one of classroom management method. In general, a college classroom in Indonesia applying linear layout seating arrangement with the front of the classroom as its orientation. Observations carried out on two classrooms and 70 students of Interior Design Major at Faculty of Art and Design in ITB. Petrel software were used to generate data such as image density deployment in a calssroom.The results of the analysis of observational data indicates that in the linear seating arrangement,which is usually applied in a classroom, a high density of students sitting position occurs in the area behind the classroom or the most distant from the source material. It is known to potentially create an unproper classroom atmosphere for a lecture to be established. Keywords: layout, room, position, seat